Improvement of Quality TSS Onion Seeds Red (Allium ascalonicum L.) with Lime as a Material Coating - Kurnia Adisya Septyaputri; Sutini Sutini; Makhziah Makhziah (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2026)
The availability of shallot seeds is a major problem in shallot cultivation; therefore, True Shallot Seed is used to overcome this problem. To make the use of TSS seeds more optimal, their germination and growth strength must be increased, one of which is by providing seed coating treatment to TSS seeds. Seed coating aims to improve and maintain seed quality, protect seeds from pathogen attacks and unfavorable environmental conditions, and support plant growth. The purpose of this study was to improve the quality of shallot TSS seeds. The experiment was conducted using a completely randomized design method with six levels and three replications. Seed coating treatments included (1) No Treatment (Control); (2) Dolomites; (2) Gypsum; (3) Quicklime; (4) Talc; (5) Pumice. The results showed that the best treatment was Gypsum, which increased the parameters of maximum growth potential, germination power, and growth synchrony. Coating seeds with Gypsum gave better results than seeds without coating treatment. The use of Gypsum as a coating material can be used as a simple and inexpensive alternative technology to improve the quality of shallot TSS seeds, making it suitable for adoption on a production and cultivation scale.